2011
DOI: 10.1111/j.1600-0722.2011.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Enamel proteins and proteases in Mmp20 and Klk4 null and double‐null mice

Abstract: Matrix metalloproteinase 20 (MMP20) and kallikrein-related peptidase 4 (KLK4) are thought to be necessary to clear proteins from the enamel matrix of developing teeth. We characterized Mmp20 and Klk4 null mice to better understand their roles in matrix degradation and removal. Histological examination showed retained organic matrix in Mmp20, Klk4, and Mmp20/Klk4 double-null mouse enamel matrix, but not in the wild-type. X-gal histostaining of Mmp20 null mice heterozygous for the Klk4 knockout/lacZ knockin show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 55 publications
1
64
0
3
Order By: Relevance
“…The present result, possibly reflecting low MMP20 expression would be in line with the result of Bourd-Boittin and coworkers 26 obtained using maristat-treated tooth germs and also with the observations in Mmp20 null and Mmp20 + Klk4 double null mice. 22,28,30 In the present study, amoxicillin treatment reduced the extent of enamel measured as the vertical enamel height/ crown height ratio from the whole tooth photographs, indicating delayed commencement of secretion by ameloblasts. Earlier we reported that amoxicillin increased the thickness of developing enamel.…”
Section: Discussionmentioning
confidence: 92%
“…The present result, possibly reflecting low MMP20 expression would be in line with the result of Bourd-Boittin and coworkers 26 obtained using maristat-treated tooth germs and also with the observations in Mmp20 null and Mmp20 + Klk4 double null mice. 22,28,30 In the present study, amoxicillin treatment reduced the extent of enamel measured as the vertical enamel height/ crown height ratio from the whole tooth photographs, indicating delayed commencement of secretion by ameloblasts. Earlier we reported that amoxicillin increased the thickness of developing enamel.…”
Section: Discussionmentioning
confidence: 92%
“…2011). In brief, D14 first molars were harvested and, for 4 molars collected from one mouse, incubated in 1 mL of 0.17 N HCl/0.95% formic acid for 2 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…MMP-20 lokalizuje się na chromosomie 11 i jest to gen autosomalny recesywny. Podczas badań na zębach myszy wykazano, że zarówno delecja genu AMELX, jak i MMP-20 powodowała powstawanie szkliwa o chropowatej powierzchni bez struktury pryzmatycznej (15).…”
Section: Odontogenezaunclassified